Phytopharmaca: Metabolomics in herbal science - Khatib, Alfi (2020)
The use of metabolomics in phytopharmaca study is currently becoming a trend. This approach focuses on comprehensive analysis of all metabolites in the sample leading to an unbiased conclusion. In this presentation, several applications of metabolomics to support the traditional medicinal claim of some herbs are discussed includng Clinacanthus nutans, Momordica charantia, and Psychotria malayana. Several instrumental platforms were used such as liquid chromatography tandem mass spectrometry, gas chromatography tandem mass spectrometry, nuclear magnetic resonance spectroscopy, and infra red spectroscopy.